Gromov width of symplectic toric manifolds associated with graphs - Choi, Suyoung; Hwang, Taekgyu (International Journal of Mathematics, 2023)
We give an explicit formula for the Gromov width for a class of symplectic toric manifolds constructed from simple graphs. As a corollary, we show a version of non-squeezing theorem with respect to the inclusion of connected graphs.
Keywords: graph associahedron; Gromov width; Hamiltonian torus action; Seidel representation